The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3892/ol.2015.3335
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-epidemiology of neuroblastoma in north east Egypt: A 5-year multicenter study

Abstract: Abstract. Neuroblastoma, an embryonal malignancy of the sympathetic nervous system, is the most frequent extracranial solid tumor The clinico-epidemiological features of neuroblastoma in infants and children were investigated between January 2005 and January 2010 at the Pediatric Oncology units of Mansoura, Zagazig, and Tanta University Children's Hospitals (Egypt). Of 142 cases of neuroblastoma, 10 were omitted from the study due to defective data. The median age of the patients was 30 months, with 75.8% aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 31 publications
2
15
1
Order By: Relevance
“…The overall AIR we calculated for SEE (10.1) is comparable to the respective rate (10.9) reported in another European study including 59 registries in 19 countries participating in the Automated Childhood Cancer Information System (1978–1997) and ranging from 9 in the British Isles to 12 in Western‐Southern Europe, but higher than those reported for the well‐controlled health care systems of the Nordic countries (Denmark: 8.6, 1981–2000; Sweden: 7, 1983–2010) . However, much lower rates are reported in the less affluent African, Southern‐Eastern Asian and Southern American countries …”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The overall AIR we calculated for SEE (10.1) is comparable to the respective rate (10.9) reported in another European study including 59 registries in 19 countries participating in the Automated Childhood Cancer Information System (1978–1997) and ranging from 9 in the British Isles to 12 in Western‐Southern Europe, but higher than those reported for the well‐controlled health care systems of the Nordic countries (Denmark: 8.6, 1981–2000; Sweden: 7, 1983–2010) . However, much lower rates are reported in the less affluent African, Southern‐Eastern Asian and Southern American countries …”
Section: Discussionsupporting
confidence: 74%
“…4,27 However, much lower rates are reported in the less affluent African, Southern-Eastern Asian and Southern American countries. 1,2,[28][29][30][31] The association of higher incidence rates of neuroblastoma with higher HDI in our study was restricted to cases diagnosed before the age of 5 years, when most of the cases are diagnosed. The differences by socioeconomic status have been traditionally attributed to the availability of modern imaging technology, provision of health care services and quality of cancer registration.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an Italian neuroblastoma cohort study reported that stage 4S NBL had a significant peak among July births; however no trend in the date of diagnosis was found [17]. In the present study, we could not classify the patients' stages; however, stage 4S NBL accounts for less than 5% of all NBL cases, so our seasonal NBL pattern is surely different from that reported in the Italian study [18]. With regards to AML, while ALL and AML are biologically different diseases with distinct etiologies [19], it is possible that different infectious agents play a role in the development of both.…”
Section: Discussioncontrasting
confidence: 88%
“…This study represented the first documented multicenter retrospective cohort study of NB in sub‐Saharan Africa. Although the majority of cases were diagnosed in the 18‐ to 60‐month age group, similar to international trends, the median age was higher at 39.9 months compared with 19 months in the United States (HIC) or 33.2 months in Egypt (MIC) …”
Section: Discussionsupporting
confidence: 61%